Formal Grammar 14th International Conference, FG 2009, Bordeaux, France, July 25-26, 2009, Revised Selected Papers - Groote, Philippe; Egg, Markus; Kallmeyer, Laura; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 14th International Conference on Formal Grammar 2009, held in Bordeaux, France, in July 2009. The 13 revised full papers presented, including two invited talks, were carefully reviewed and selected from 26 submissions. These articles in this book give an overview of new and original research on formal grammar, mathematical linguistics and the application of formal and mathematical methods to the study of natural language.
Keywords: Computer science; Algebra -- Data processing; Artificial intelligence; Computational linguistics; Grammar, Comparative and general; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Computation by Abstract Devices; Symbolic and Algebraic Manipulation; Computational Linguistics; Grammar